Oral Chondrolipoma: A Rare Case Report - Shubhangi Mani; Manas Bajpai; Saurabh L. Sabnis (The Turkish Journal of Ear Nose and Throat)
Chondrolipoma is a rare histological variant of lipoma characterised by the formation of mature hyaline cartilage along with adipose tissue. Chondrolipomas are rare in the oral cavity, with very few cases reported to date. Intra-orally chondrolipoma have been reported most commonly in the tongue, followed by the lower lip, vestibule, and floor of the mouth. Because of the very few cases of chondrolipoma reported in the oral cavity, there is a paucity of information regarding their biological behaviour and clinical outcome. We report a rare case of oral chondrolipoma occurring on the right maxillary attached gingiva; the lesion was initially diagnosed as fibroma. Histopathological examination rendered the diagnosis of chondrolipoma.